Bài 1:
a,27x3+27x2+9x+1a,27x3+27x2+9x+1
=(3x)3+3.(3x)2.1+3.3x.12+13=(3x)3+3.(3x)2.1+3.3x.12+13
=(3x+1)3=(3x+1)3
b,x3+3√2x2y+6xy2+2√2y3b,x3+32x2y+6xy2+22y3
=x3+3.x2.√2y+3.x.(√2y)2+(√2y)3=x3+3.x2.2y+3.x.(2y)2+(2y)3
=(x+√2y)3=(x+2y)3
Bài 2:
a,x3+9x2+27x+27=0a,x3+9x2+27x+27=0
⇔(x+3)3=0⇔(x+3)3=0
⇔x+3=0⇔x=−3⇔x+3=0⇔x=−3
b,(x+1)3−x(x−2)2+x−1=0b,(x+1)3−x(x−2)2+x−1=0
⇔x3+3x2+3x+1−x3−4x2+4x+x−1=0⇔x3+3x2+3x+1−x3−4x2+4x+x−1=0
⇔−x2+8x=0⇔−x2+8x=0
⇔−x(x−8)=0
27x³ - 27x² + 3x + 1
= 27x³ - 9x² - 18x² - 3x + 6x + 1
= (27x³ - 9x²) - (18x² - 6x) - (3x - 1)
= 9x² (3x - 1) - 6x (3x - 1) - (3x - 1)
= (3x - 1) (9x² - 6x - 1)